2020
DOI: 10.1590/1678-4685-gmb-2019-0070
|View full text |Cite
|
Sign up to set email alerts
|

Persistent double strand break accumulation does not precede cell death in an Olaparib-sensitive BRCA-deficient colorectal cancer cell model

Abstract: The poly (adenosine diphosphate (ADP)-ribosyl) polymerase inhibitors (PARPi) selectively kill cancer cells with BRCA1 or BRCA2 (BRCA)-mutations. It has been proposed that cell death induction after PARPi depends on unrepaired double strand breaks (DSBs) that accumulate due to the homologous recombination deficiency of BRCA-mutated cells. Such accumulation of DSBs is inferred mainly from the high levels of DNA damage markers like phosphorylated histone H2AX. Herein, we developed a model of isogenic cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It has already been explained how, in cells that harbour HR system mutations leading to defective DNA double-strand break repair, as in BRCAm patients, genome stability is maintained through the activity of BER and PARP enzymes. However, Paviolo et al [ 39 ] demonstrated that in PARPi-treated BRCA-defective CRC samples, even though DSBs are generated, they are not directly responsible for cell death. Indeed, more than DSBs, it was proven that rapid and anomalous repair of these defects, through means of DNA repair mechanisms different from HRD, leads to severe chromosomic aberrations which are the cause of cell death.…”
Section: Crcmentioning
confidence: 99%
“…It has already been explained how, in cells that harbour HR system mutations leading to defective DNA double-strand break repair, as in BRCAm patients, genome stability is maintained through the activity of BER and PARP enzymes. However, Paviolo et al [ 39 ] demonstrated that in PARPi-treated BRCA-defective CRC samples, even though DSBs are generated, they are not directly responsible for cell death. Indeed, more than DSBs, it was proven that rapid and anomalous repair of these defects, through means of DNA repair mechanisms different from HRD, leads to severe chromosomic aberrations which are the cause of cell death.…”
Section: Crcmentioning
confidence: 99%
“…Several studies propose that PARPIs prompt cell death by accumulating unrepaired DSBs due to the HR deficiency in BRCA -mutated cells. Even though BRCA mutations are infrequent in CRC, the PARPIs are undergoing several clinical trial investigations as single agents or combined with radiation or chemotherapeutic agents [ 138 , 139 , 140 , 141 , 142 , 143 , 144 ].…”
Section: Fa Components As Promising Therapeutic Targets In Crcmentioning
confidence: 99%
“…In this regard, Paviolo et al [ 140 ] have shown that the treatment of BRCA-deficient CRC cell lines with olaparib may lead to genomic instability and cell death [ 140 ]. Moreover, Reisländer et al [ 144 ] have revealed that the treatment of BRCA1- or BRCA2-deficient CRC cell lines with olaparib boosted the up-regulation of innate immune response genes upon intrinsically high levels of DNA damage [ 144 ].…”
Section: Fa Components As Promising Therapeutic Targets In Crcmentioning
confidence: 99%
“…The emergence of PLK1 inhibition as a strategy to treat TNBC and BRCA1-deificient cancers opens the discussion of whether such strategy can be complementary and/or alternative to PARPi. The available evidence indicates that PARPi and PLK1i work through different molecular mechanisms [45,[110][111][112].For instance, PLK1 inhibition shows only mild synthetic lethal activity with BRCA2-deficient cells [45], while PARP inhibition induces synthetic lethality both with BRCA1 and BRCA2, as well as with other related proteins that trigger homology-directed repair deficiencies [113]. In addition, while some TNBCs display sensitivity to PARP inhibition [114], this response does not seems to be selective for all types of TNBCs, in contrast to the more general link found between this cancer subtype and PLK1i sensitivity [45,[84][85][86].…”
Section: Parp and Plk1 Inhibitors: Complementary Or Alternative?mentioning
confidence: 99%